Parenting style, young driver compliance and the imposition of additional driving restrictions within graduated driver licensing systems. (September 2020) - Bates, Lyndel; Somoray, Klaire; Lennon, Alexia
Highlights: Surveys with parents and young drivers indicates that parenting styles affect young driver compliance with provisional driving laws. Parents with higher levels of control are more likely to have children that comply with provisional driving laws. Parents with higher levels of support are more likely to offer practical driving assistance. Those whose parents had higher levels of control and lower levels of support were more likely to have additional driving restrictions. Abstract: Provisional (or intermediate) drivers do not always comply with graduated driver licensing restrictions and road laws. The aim of this study was to explore the effect of parenting style on young driver compliance with licensing restrictions. Two surveys, the first a sample of parents of provisionally licensed drivers (n = 101) from Queensland and the Australian Capital Territory (Australia), while the second, and separate sample, was of provisionally licensed drivers (n = 132) from Queensland. A series of regression analyses identified that parents who reported higher levels of control were more likely to feel responsible for their child's driving and to have a child that complied with licensing restrictions. Parents who reported higher levels of support were more likely to offer their child practical assistance in order to help them to comply with licensing restrictions. Young drivers who reported that their parents had higher levels of control were more likely to indicate that they complied with restrictions. Given that parenting style appears to influence provisional driver compliance with licensing requirements, there may be an opportunity to develop interventions to enhance compliance.